Legal Protection For Cessionaris Of Fiduciary Collateral Objects In The Form Of Receivables Through Cessie As A Form Of Transfer Of Taxable Goods - Tandiono, Sudargo; Rini, Indrati (Universitas Islam Malang, 2024)
The existence of a collateral object is intended as a form of protection for creditors if the debtor experiences delinquency, which makes it easier for creditors to collect repayment from the collateral object. However, in terms of the object of collateral in the form of accounts receivable, how valid is it as a form of transfer through a cessie. The normative legal approach using the statute approach is applied in the research methodology of this research. The results of the analysis show that the parties most at risk in transferring fiduciary collateral with objects of receivables through a cessie are Cedents (old creditors) and Cessionaris (new creditors). On the other hand, even though there is destruction of the collateral object on the transferred receivable due to payment by the debtor, the tax that has been credited cannot be adjusted in value. Therefore, it is very detrimental for cedents and cessionaries to deal with these problems.